Stress-Induced Polyploid Giant Cancer Cells: Unique Way of Formation and Non-Negligible Characteristics - Song, Yanwei; Zhao, Yucui; Deng, Zheng; Zhao, Ruyi; Huang, Qian (Frontiers in Oncology, 2021)
Polyploidy is a conserved mechanism in cell development and stress responses. Multiple stresses of treatment, including radiation and chemotherapy drugs, can induce the polyploidization of tumor cells. Through endoreplication or cell fusion, diploid tumor cells convert into giant tumor cells with single large nuclei or multiple small nucleuses. Some of the stress induced colossal cells, which were previously thought to be senescent and have no ability to proliferate, can escape the fate of death by a special way. They can remain alive at least before producing progeny cells through asymmetric cell division, a depolyploidization way named neosis. Those large and danger cells are recognized as Polyploid Giant Cancer Cells (PGCCs). Such cells are under suspicion of being highly related to tumor recurrence and metastasis after treatment, and can bring new targets for cancer therapy. However, differences in formation mechanisms between PGCCs and well-accepted polyploid cancer cells are largely unknown. In this review, the methods used in different studies to induce polyploid cells are summarized, and several mechanisms of polyploidization are demonstrated. Besides, we discuss some characteristics related to the poor prognosis caused by PGCCs, in order to provide readers with a more comprehensive understanding of these huge cells.